2010
DOI: 10.1074/jbc.m109.061366
|View full text |Cite
|
Sign up to set email alerts
|

Functional Oligomerization of the Saccharomyces cerevisiae Isoprenylcysteine Carboxyl Methyltransferase, Ste14p

Abstract: The isoprenylcysteine carboxyl methyltransferase (Icmt) from Saccharomyces cerevisiae, also designated Ste14p, is a 26-kDa integral membrane protein that contains six transmembrane spanning segments. This protein is localized to the endoplasmic reticulum membrane where it performs the methylation step of the CAAX post-translational processing pathway. Sequence analysis reveals a putative GXXXG dimerization motif located in transmembrane 1 of Ste14p, but it is not known whether Ste14p forms or functions as a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
(59 reference statements)
0
15
0
1
Order By: Relevance
“…Residues on M1 and M3 that make contacts between these helices are drawn as sticks and coloured magenta. Because the M1 and M2 helices are not present in Saccharomyces cerevisiae ICMT enzyme, we hypothesize that the GxxxG motif that is present in the first transmembrane helix of yeast ICMT (equivalent to M3 of beetle ICMT) may cause dimerization of the yeast enzyme through packing of these helices 41 , whereas ICMT enzymes that contain M1 and M2, which includes human and beetle ICMT, are monomeric. The location of a PreScission protease cleavage site (PS site) that was inserted in the connection between the M2 and M3 helices (introduced at Asn58) for experiments outlined in this figure is indicated.…”
Section: Extended Datamentioning
confidence: 99%
“…Residues on M1 and M3 that make contacts between these helices are drawn as sticks and coloured magenta. Because the M1 and M2 helices are not present in Saccharomyces cerevisiae ICMT enzyme, we hypothesize that the GxxxG motif that is present in the first transmembrane helix of yeast ICMT (equivalent to M3 of beetle ICMT) may cause dimerization of the yeast enzyme through packing of these helices 41 , whereas ICMT enzymes that contain M1 and M2, which includes human and beetle ICMT, are monomeric. The location of a PreScission protease cleavage site (PS site) that was inserted in the connection between the M2 and M3 helices (introduced at Asn58) for experiments outlined in this figure is indicated.…”
Section: Extended Datamentioning
confidence: 99%
“…dimerization) through interactions of helical transmembrane domains (28). Although the oligomeric state of ICMT has not been definitively resolved, it has been suggested that it may function as a dimer or higher order oligomer (29). To determine the importance of the residues in the GXXXG-like motif for ICMT activity, we mutated three residues of Ag ICMT in this motif (Ala-68, Gly-72, and Ser-76).…”
Section: M) (21)mentioning
confidence: 99%
“…Recent evidence suggests that Ste14 forms a dimer or other higher-order oligomer through a GXXXG motif in its first transmembrane span (104,218). Heterologous expression of either the Schizosaccharomyces pombe STE14 homolog, Mam4, or the mammalian ICMT can functionally complement a yeast ste14⌬ mutant, indicating that distant homologs have conserved function (68,220).…”
Section: Ste14 the Founding Member Of The Isoprenylcysteine Carboxylmentioning
confidence: 99%